Efeitos adversos da morfina, metadona e tramadol no pós-operatório de cães submetidos à cirurgia da coluna vertebral - Ripplinger, Angel (2017)
Postoperative pain in dogs undergoing vertebral surgery is classified as severe and is important an adequate approach to it, because it can influences recovery time, quality of life and surgery outcome. Opioids are indicating for postoperative pain treatment in these surgeries. Opioids may have adverse effects that may require attention. There are few clinical studies that present the adverse effects of these analgesics in canine postoperative period. The aim of this retrospective study was to present the adverse effects of morphine, methadone and tramadol in canine vertebral surgery postoperative period. There were revised the postoperative records of 180 dogs and the changes resulted from the opioids use were noted. The adverse effects observed were anorexia, hypophagia, vomiting, vocalization, bradycardia, hypothermia, panting, sedation. Pain was also observed in some dogs. A significant difference was found in anorexia between dogs treated with morphine and tramadol and methadone and tramadol. Significant difference was also found in pain between dogs treated with morphine and tramadol. The association of metamizole and morphine or metamizole and methadone was not different in relation to the adverse effects. There was also no difference with the dosage variation and the adverse effects. In conclusion, morphine, methadone and tramadol have adverse effects when used for pain control in the postoperative period of dogs submitted to vertebral surgery. Anorexia, hypophagia and emesis were frequent adverse effects observed with morphine and methadone and, despite tramadol presented less adverse effects, its use may be not beneficial in the studied doses when we consider the degree of pain, however more controlled studies with clinical situation are needed to confirm this.